Correlation of fruit fly (Diptera: Tephritidae) infestation of major mango cultivars in Borgou (Benin) with abiotic and biotic factors and assessment of damage - Vayssières, Jean-François; Korie, S.; Ayegnon, D. (Elsevier, 2009)
Fruit flies associated with mango trees were monitored in two orchards in Benin using traps baited withmethyl eugenol, terpinyl acetate andToruladuring 2005–2006. Population fluctuations were analysedwith respect to environmental factors including air temperature, relative humidity and rainfall in relationto different mango cultivars. Mangoes were sampled every two weeks during the two crop years, toassess the damage caused by these quarantine pests on ten main cultivars. Three native species ofCeratitisand a recently described new exotic species,Bactrocera invadensmade up the complex ofeconomically significant fruit flies associated with the mango tree in Borgou.Ceratitisspecies occurredduring the dry season and the main species,Ceratitis cosyra, reached a peak at the end of the dry season.B. invadenspopulations were scarce during the dry season, but increased steadily from the end of April toreach a peak at the end of June during the rainy season. Regression analyses indicated that minimum–maximum temperature, relative humidity and rainfall were the major climatic factors influencing flypopulations. Daily rainfall was the factor showing the strongest positive correlation withB. invadenspopulations. Host plant was another essential factor influencing the population fluctuations. Trappingand rearing data indicated thatCeratitis quinariaandCeratitis silvestrii, were abundant only in the dryseason, causing damage only to early cultivars.C. cosyra, also common during the dry season, attackedboth early cultivars or mid season cultivars. A consistent population increase ofB. invadensin the earlyrainy season caused considerable damage to mid season and late cultivars. The seasonal increase of theB.invadenspopulation coincided with the fruiting period of the main mango cultivars in this NorthernGuinean savannah, but mango availability influenced the population of this new invasive species onlywhen the rains had arrived. Mean damage on mangoes for the two seasons and two studied orchardsincreased from 17% in early April to 73% at mid June.